POLIGAMI DALAM TINJAUAN HIFDZ AL-NASL - Karimullah, Suud Sarim (MADDIKA : Journal of Islamic Family Law, 2023)
When talking about polygamy, it is often seen from the existence and perspective of meeting the biological needs of men. Polygamy is seen as a form of unequal relationship in marriage, so the losers are women. Polygamy always creates a negative perception even though many polygamists are still carried out illegally. Regarding the problem of polygamy, it is necessary to conduct a review that looks at the benefits to produce a comprehensive study. So, in this case, the issue of polygamy is studied through an examination of hifdz al-nasl, which is one of the concepts of maqashid al-shari'ah. At the same time, library research is this type of research with the nature of a descriptive-analytical study that systematically describes the facts found accurately and carefully through a review of hifdz al-nasl. This research concludes that polygamy is a wisdom given by Allah to humans and does not violate the purpose of maqashid al-shari'ah to continue protecting offspring (hifdz al-nasl) while still producing because a man will still be able to produce even though they are old. Meanwhile, women are limited by menopause so that when that period has arrived, the female reproductive organs can no longer function generally for fertilization.